Why would financial bubbles evolve after new technologies? - Haim Kedar-Levy (The Journal of Entrepreneurial Finance and Business Ventures, 2007)
This paper presents an equity market where the value of a new technology is infrequently observable while the equity claim of the asset is continuously traded. We clear the stock market between two optimal asset allocation strategies, speculative vs. fundamental, adopted by risk-averse investors who differ in their risk-aversion. The stock price path maintains a potential for endogenous bubbles or under-pricing vs. the asset as a function of total funds invested in the stock by each investor type. Bubbles grow exponentially if speculation dominates but if the fundamental strategy dominates, the stock's growth rate and its volatility will decline.
Keywords: 650